A case of transorbital intracranial injury presenting with subtle neurological deficit - Parajuli, Anil; Bastola, Jyoti; Shrestha, Gulshan Bahadur; Shrestha, Jyoti Baba (Nepalese Journal of Ophthalmology, 2016)
Background: Ocular trauma is a major cause of visual morbidity. Objective: To present a rare case of transorbital intracranial injury extending up to the left internal carotid artery (ICA) with no other systemic neural deficit except for the ocular manifestations. Case: A 14-year-old female presented to our out-patient department (OPD) with the history of trauma to her left eye with stumps of bamboo shoots secondary to a fall injury. Examination and investigations revealed a foreign body extending from left inferior conjunctival fornix into the intracranial cavity, occluding the various segments of left ICA. The patient subsquently underwent craniotomy and foreign body removal by a combined team of neurosurgeons and ophthalmologists. On discharge, the patient had slight improvement in extraocular motility of her left eye. However the trauma rendered the affected eye, non-seeing. Conclusion: The intracranial extent of a foreign body entering the cranium via the transorbital route cannot be judged merely by the clinical findings of the nervous system and ocular examination. These patients need timely management by the combined effort of ophthalmologists, neurosurgeons and radiologists.